Clinical Profile, Radiological Resolution and Risk Factors Associated with Community Acquired Pneumonia - Singh, Srijana Dongol; Shrestha, Narayan Charan; Joshi, Anish (Journal of Nepal Paediatric Society, 2018)
Introduction Pneumonia is a widespread and commonest infectious lung disease that causes inflammation which lead to reduced oxygenation. Indeed, it is the leading cause of child death in the world. The study was carried out to fine out the demographic, clinical characteristics and radiologic resolution of Pneumonia in children between 2 months to 16 years of age. Material and Methods A prospective study done in 121 cases over 18 month period in patients admitted in pediatric department of Dhulikhel hospital. Demography, clinical profile, diagnosis, Down’s scoring at presentation, response of treatment and risk factor for fetal Community acquired pneumonia were analyzed using descriptive statics. Chest radiography was done on admission and every 2 weeks until its complete resolution occurred. Results A total of 121 patients with community acquired pneumonia were enrolled. The male and female ratio was 1.69:1. Among all age group it was most significantly common in children less than 1 year (p=.022).The common symptoms of Community acquired pneumonia observed in this study were cough (80%), fever (66%) and shortness of breath (38.8%). On chest roentgenogram right middle zone(47.9%) was most frequently involved. The total leukocyte count had low degree of association with pneumonia. More than half of patients (54.08%) with community acquired pneumonia had radiographic resolution at 2 weeks. The respiratory distress was significantly high (p<0.0001) in children who delayed to seek medical treatment in a health facility by three days.Anemia, lymphopenia, thrombocytopenia, sepsis and hemorrhagic pleural effusion were the clinical characteristics associated withfatal Community acquired pneumonia Conclusion Clinical presentations variesin Community acquired pneumonia with different age groups. Chest radiography is still best investigation for the diagnosis of pneumonia and most of the radiological clearance occurs in 2 weeks.